The impact of migration on trade - Murat Genç (IZA World of Labor, 2014)
International trade and migration are two important dimensions of globalization. Although governments have been very willing to open their borders to trade, they have not been so liberal in their immigration policies. It has been suggested, however, that a causal positive link might exist between immigration and trade. Could governments further increase international trade by also opening their doors to immigrants? If they could, does it matter what type of immigrants are encouraged? And is there a saturation level of immigrants after which this positive impact disappears?
Keywords: F14; F22; J15; 330; migration; international trade; trade facilitation